Determination of vehicle wheel wander for urban roadways in Costa Rica - Morris Mitchell, Velvet (2025)
The main objective of this project consists in estimate a value of wheel wander representative of Costa Rican roadways, which could be used for pavements design and testing. In order to achieve the objective, wheel wander was measured and computed in 6 different stations with similar characteristics located in national routes from the Great Metropolitan Area of Costa Rica. Wheel wander is the scatter of vehicles along the length of the lane. Drivers usually follow a normal distribution pattern. In the wheel paths that most drivers follow, traffic load will be higher causing rutting in the pavement. Therefore, in roadways where wheel wander is high, the traffic load is distributed along the lane width, increasing the design life. For each station only the outer lane, the closest to the camera, was used. These stations are located in National Route 3, National Route 2, National Route 202, National Route 32, National Route 39 and National Route 108.These routes were chosen because of their high truck traffic volume. In each station, a camera was placed roadside. Also lines were drawn covering more than the half of the lane cross section. The position of both heavy and light vehicles was measured. Standard deviation and confidence interval for variance equations were used to determine the wheel wander. Results show that the mean and 95% confidence interval of wheel wander is drastically higher that the value of 10 cm used by the LanammeUCR for accelerated pavements testing.